Scratching the surface: The diversity and roles of triterpenoids in plant cuticular waxes - Priyanka Trivedi; Gang-Shuai Liu; Linards Klavins; Raktim Bhattacharya; Soile Jokipii-Lukkari; Adinpunya Mitra; Maris Klavins; Da-qi Fu; Laura Jaakola; Anna Szakiel; Katja Karppinen (Phytochemistry Reviews, 2026)
The cuticle and cuticular waxes play vital roles as the interface between a plant and its environment. Cuticular waxes are composed of very long-chain fatty acids (VLCFAs) and their derivatives as well as triterpenoids, which are specialized metabolites. Although triterpenoids constitute a major fraction of cuticular waxes, their functions remain poorly understood. In this review, we provide an overview of the chemical diversity of triterpenoids in the cuticular waxes of leaves and fruits of angiosperms and discuss changes in triterpenoid content during their development. The methods and challenges for the analysis of cuticular wax triterpenoids are summarized. The biosynthesis of triterpenoids is also reviewed along with recent knowledge of the potential mechanisms of triterpenoid transportation and secretion from the site of biosynthesis to the plant surface. Considering ongoing climate change, the current understanding of the effects of environmental conditions and abiotic stress factors on cuticular wax triterpenoids is reviewed. We also present an overview of the current knowledge on the roles of triterpenoids in cuticular waxes in transpiration and defense against biotic stressors and their possible role in cuticle stabilization. Moreover, owing to the generally high levels of triterpenoids in fruit cuticular waxes, the provided information on the variation and role of cuticular wax triterpenoids during postharvest fruit storage might help in the development of strategies for better fruit quality maintenance and preservation.